2012
DOI: 10.1111/jfpp.12050
|View full text |Cite
|
Sign up to set email alerts
|

Scale Up of Sugarcane Vinegar Production by Recycling of Successive Fermentation Batches and its Organoleptic Evaluation

Abstract: Sugarcane with a high content of sugar is a potential substrate for making vinegar through alcoholic and acetous fermentation. As an alternative to the longer traditional batch scale vinegar fermentation, a fermentation process involving successive discontinuous cycles of acetification was developed. The cycles standardized for 3 days of shaking (75 rpm) and addition of (NH4) 2SO4 and KH2PO4 were recycled with previous lots of fermentation resulting in vinegar production with a time period of 7.6 days compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…However, it may be called as ‘successive discontinuous cycles of acetification’ as described by Kocher et al . (), wherein at the end of every cycle, the optimized volume of reactor is collected as vinegar and refilled with initial medium (fresh fermented ethanol). The semi‐continuous acetification results show that LSM‐AAB shortens both the adaptation and the operational periods significantly (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, it may be called as ‘successive discontinuous cycles of acetification’ as described by Kocher et al . (), wherein at the end of every cycle, the optimized volume of reactor is collected as vinegar and refilled with initial medium (fresh fermented ethanol). The semi‐continuous acetification results show that LSM‐AAB shortens both the adaptation and the operational periods significantly (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It may be called as ‘successive discontinuous cycles of acetification’ (Kocher et al . ). However, to maximize the activity of acetic acid bacteria (AAB) as they oxidize ethanol (ET) to acetic acid (AA), it requires a high rate of oxygen transfer at the air : liquid interface (Tesfaye et al .…”
Section: Introductionmentioning
confidence: 97%
“…Jimoh et al (2009) reported that they obtained 9.30% vol/vol after 7 days of fermentation, while Choonut et al (2014) reported the maximum yield of ethanol (9.69 g/L) achieved after 72 h from inoculum. In the same fermentation time, Kocher et al (2014) observed an ethanol production of 9.40% vol/ vol in wines from sugarcane. In mango wines, Li et al (2012) registered the production of 6.84, 6.33, and 8.05% vol/vol ethanol.…”
Section: Characterization Of the Three Pineapple Winesmentioning
confidence: 69%
“…In the same fermentation time, Kocher et al . () observed an ethanol production of 9.40% vol/vol in wines from sugarcane. In mango wines, Li et al .…”
Section: Resultsmentioning
confidence: 97%